Effects of Synchronous and Asynchronous Approaches in Geometry Learning to Stimulate Students' Critical Thinking - Aminudin, Mohamad; Maharani, Hevy Risqi; Fauzanah, Aldira Eka (Universitas Islam Sultan Agung, 2023)
Geometry learning has an important role in stimulating critical thinking. During the Covid-19 pandemic, synchronous and asynchronous approaches became an alternative in geometry learning. The purpose of this study is to investigate the effectiveness of geometry learning by combining synchronous and asynchronous approaches in stimulating critical thinking. This study used a mixed design, namely quantitative and qualitative approaches. The sample was mathematics education students who had taken basic calculus and mathematical logic courses. Quantitative data collection used critical thinking worksheets and questionnaires to measure student activities and responses. Qualitative data collection through learning video recordings and researcher notes during learning. The results showed that student activity was high. Details can be explained in the discussion section.